The Effect of Compensation,Work Motivation, Andwork Discipline on Work Achievement of Subdistrict Office Employees Koto Baru City Sungai Penuh - Hendra, Hendra (The Future of Education Journal, 2025)
This study aims to find out: 1) To determine the effect of compensation on the work performance of employees of the Koto Baru Sub-District Office of Sungai Full City partially and how much 2) To determine the effect of work motivation on the work performance of employees of the Koto Baru Sub-District Office of Sungai Full City partially and how much magnitude 3) To determine the effect of work discipline on the work performance of employees of the Koto Baru Sub-District Office of Sungai Full City partially and how much 4) To determine the effect of compensation, work motivation and work discipline on the work performance of employees of the Koto Baru Sub-District Office of Sungai Full City simultaneously and how big. The population in this study were employees of the Koto Baru Sub-District Office of Sungai Full City with a total of 11 employees. Furthermore, it was found that all populations were used as samples of 11 employees with saturated sampling techniques. The data analysis tool used is multiple linear regression analysis. Compensation has a positive and significant effect on employee work performance as evidenced by tcount > ttable or (5.838 > 2.36462) and sig < α (0.001 < 0.05), so Ho is rejected and Ha is accepted. The magnitude of the effect is 3.6%. Work motivation has no effect on employee work performance, as evidenced by tcount < ttable or (-1.009 < 2.36462) and sig > α (0.346 > 0.05), so Ho is accepted and Ha is rejected. The magnitude of the effect is 15.9%. Work discipline has a negative and significant effect on employee work performance, as evidenced by tcount < ttable or (-6.023 < 2.36462) and sig < α (0.001 < 0.05), so Ho is rejected and Ha is accepted. The magnitude of the effect is 9.1%. Compensation, work motivation, and work discipline have a positive and significant effect on the work performance of employees at the Koto Baru Subdistrict Office, Sungai Banyak City, this is proven by Fcount > Ftable or (15.352 > 4.35) and sig < α (0.002 < 0.05), then Ho is rejected and Ha is accepted. The magnitude of the effect is 86.8%.